Perception of peacekeeping activities in Africa by the local population (on the example of Mali) - S. A. Bokeriya; A. R. Andronova (RUDN journal of Sociology)
The article considers the perception of peacekeeping activities by the local population in Africa on the example of Mali. In recent years, peacekeepers have been increasingly criticized by the civilian population, despite reforms of the UN and regional organizations. The main reasons, as a rule, are as follows: lack of fi support, inability of peacekeepers to achieve the goals of the mandate, and their abuse of authority. However, sociological surveys show deeper reasons for criticism of peacekeeping missions. In Mali, the public dissatisfaction with the activities of the UN peacekeeping mission led to protests and the government’s demand to withdraw the peacekeeping contingent from Mali. This precedent actualizes the issues of the reasons for the current situation and of the perception of peacekeepers by the local population. This study aims at examining the dynamics of public trust in peacekeepers and the reasons for distrust in peacekeeping missions. Based on the comparative analysis of sociological surveys (questionnaires, focus groups and interviews) conducted among the local population by two international research centers - the Friedrich Ebert Foundation (FES) from 2012 to 2024 and the Stockholm International Peace Research Institute (SIPRI) from 2019 to 2022, the authors argue that the majority of Malians are satisfi with the government’s decision to stop the peacekeeping operation of the United Nations Multidimensional Integrated Stabilization Mission in Mali (MINUSMA), since they trust the national army and police much more. The research for this attitude are both objective (for example, the privileges and immunity enjoyed by peacekeepers on the territory of Mali; participation of peacekeepers in corruption schemes; their unauthorized use of force) and subjective (MINUSMA’s ignorance of local problems and of the mission’s mandate).